Nano-hydroxyapatite use in dentistry: a systematic review. (2nd April 2020) - Bordea, Ioana Roxana; Candrea, Sebastian; Alexescu, Gabriela Teodora; Bran, Simion; Băciuț, Mihaela; Băciuț, Grigore; Lucaciu, Ondine; Dinu, Cristian Mihail; Todea, Doina Adina
Abstract: Nano-hydroxyapatite (nano-HA) is a material with multiple uses due to its biocompatibility and its resemblance to the nonorganic bone structure. It is used in various dental domains such as implantology, surgery, periodontology, esthetics and prevention. The aim of this study is to provide a wide understanding of nano-HA and to promote treatments based on nanomaterials in dentistry. A search in two data bases, Scopus, and PubMED, was conducted over a 5 years period. We chose a 5 years period because this revealed the most recent published studies with the key words 'nano-HA' and 'dentistry'. A number of 32 studies were included in this systematic review. In implantology the main use of nano-HA was as a coating material for titanium implants and its effect was assessed in the matter of osteointegration and inflammatory response as well as antibacterial activity. In tissue engineering the use of nano-HA was directed to surgery and periodontology and this material was assessed mainly as a grafting material. In esthetics and prevention its use was mainly focused on dentinal hypersensitivity treatment, remineralizing potential and as bleaching co-agent. Nano-HA is a relatively novel material with outstanding physical, chemical, mechanical and biological properties that makes it suitable for multiple interventions. It outperformed most of the classic materials used in implantology and surgery but it should be further investigated for bone engineering and caries prevention therapy.